Mother–Infant Interaction and Child Brain Morphology: A Multidimensional Approach to Maternal Sensitivity. (14th October 2018) - Bernier, Annie; Dégeilh, Fanny; Leblanc, Élizabel; Daneault, Véronique; Bailey, Heidi N.; Beauchamp, Miriam H.
Abstract : Emerging research suggests that normative variation in parenting quality relates to children's brain development. However, although the young brain is presumed to be especially sensitive to environmental influence, to our knowledge only two studies have examined parenting quality with infants as it relates to indicators of brain development, and both were cross‐sectional. This longitudinal study investigated whether different components of maternal sensitivity in infancy predicted the volume of two brain structures presumed to be particularly sensitive to early experience, namely the amygdala and the hippocampus. Three dimensions of sensitivity (Cooperation/Attunement, Positivity, Accessibility/Availability) were observed in 33 mother–infant dyads at 1 year of age and children underwent structural magnetic resonance imaging at age 10. Higher maternal Accessibility/Availability during mother–infant interactions was found to be predictive of smaller right amygdala volume, while greater maternal positivity was predictive of smaller bilateral hippocampal volumes. These longitudinal findings extend those of previous cross‐sectional studies and suggest that a multidimensional approach to maternal behavior could be a fruitful way to further advance research in this area, given that different facets of parenting might be differentially predictive of distinct aspects of neurodevelopment.